2021
DOI: 10.3390/agronomy11112138
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Soil vs. Foliar Nitrogen Supply of the Whole Fertilizer Dose in Common Wheat

Abstract: Late-season N application through foliar spraying is recognized as an efficient agronomic practice for improving grain quality in common wheat, although the major part of N is still supplied by soil fertilization. This study assessed the impact of various N doses entirely applied by repeated foliar sprayings on wheat growth, yield and quality, in comparison with conventional soil fertilization management with a recommended dose of 160 kg N ha−1 as ammonium nitrate (C-M). Doses of 96, 104 and 120 kg N ha−1 as b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 33 publications
1
18
0
Order By: Relevance
“…Foliar N-fertilization has the potential to improve fertilizer-NUE. However, leaf scorching may occur after foliar N-fertilization [23,45,46], as was also observed and characterized in the present work (Figures 1 and 3). The scorching appeared as chlorosis of the leaf tip, where NH 4 + accumulation is driven by the transpiration stream [47].…”
Section: Long-term Foliar N-fertilization Responses (Second Experiment)supporting
confidence: 86%
“…Foliar N-fertilization has the potential to improve fertilizer-NUE. However, leaf scorching may occur after foliar N-fertilization [23,45,46], as was also observed and characterized in the present work (Figures 1 and 3). The scorching appeared as chlorosis of the leaf tip, where NH 4 + accumulation is driven by the transpiration stream [47].…”
Section: Long-term Foliar N-fertilization Responses (Second Experiment)supporting
confidence: 86%
“…The result of the study is in agreement with that of Al-Amin who obtained the longest panicle length from the foliar spray of 3% urea solution and the shortest one from 2% urea solution. Higher doses of N increased the panicle length per plant . The longest panicle length was observed from 6 times foliar spray of urea solution .…”
Section: Resultsmentioning
confidence: 92%
“…Soil and foliar application of fertilizers also significantly increased the grains per spike of wheat. 37,38,41 Number of Sterile Grains Panicle −1 . Nitrogen fertilizer doses and application methods showed significant effects on the unfilled grains panicle −1 of rice.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The study showed that foliar N application with urea was preferable compared to urea‐ammonium‐nitrate. Quality‐related traits were similar in the wheats with conventional and foliar treatments, indicating that foliar N application allows a reduction of total N addition by 25%–40% (Ferrari et al, 2021).…”
Section: Factors Affecting the Quantity Of Wheat Gluten Proteinsmentioning
confidence: 94%
“…In addition to the total amount of N and timing of N application, the N application strategy was studied for its impact on wheat quality‐related parameters. The impact of supplying the total amount of N by repeated foliar application was compared to conventional soil fertilization using one Italian wheat variety with high bread‐making quality grown in two seasons (Ferrari et al, 2021). All treatments received 32 kg N/ha at sowing and there was one control with no further fertilization.…”
Section: Factors Affecting the Quantity Of Wheat Gluten Proteinsmentioning
confidence: 99%